Aprendizaje organizacional en organizaciones profesionales - Arbaiza Fermini, Lydia (2002)
This work examines at the exploratory level formal or informal organizational learning mechanisms that are present in organizations of professionals from the case of studies or law firms. This first approximation results in the identification of six organizational learning mechanisms: reflection on the cases, the revision of the doctrine, the trial and error, the monitoring, the diffusion of knowledge, and the spirit of the body. There is also a tendency to favour the culture of learning through the involvement and empowerment of employees, the transformation of the role of an administrator in the role of teacher and coach and a tendency towards a horizontal and participatory structure.